III, Intermediary Divinities and Personal Piety in Ancient Greece and Ancient Mesopotamia: The Rise of Personal Religion? - Cassidy, William J.
Ph.D. dissertation; Coordinator: Mark Juergensmeyer; Order No. DA8529989; cf. DissAbstr 46,11 (1986) 3381-A.